Comparative evaluation of plasma fibrinogen degradation product and salivary fibrin precipitating factor in oral submucous fibrosis patients and betel quid chewers - B Megha; Jayaprasad Anekar; A C Ra; N Deepika; Krishna Santhosh Kumar (Wolters Kluwer Medknow Publications, 2023)
Aim and Objectives: Estimation and correlation of plasma fibrinogen degradation product (FDP) and salivary fibrin precipitating factor (FPF) in oral sub mucous fibrosis (OSMF) patients, betel quid chewers without OSMF and healthy individuals. The study aims to evaluate whether FDP and FPF can be used as a marker for development and progression of OSMF and whether there is any correlation between the two. Methodology: The study included 163 subjects grouped into three categories, Group 1, which included 54 control patients, Group 2, which included 55 betel quid chewers, and Group 3, which included 54 clinically confirmed OSMF patients. All of them were subjected to the estimation of plasma FDP and salivary FPF. Results: FDP was present in 52 (96.3%) patients in Group 3, 2 (3.6%) patients in Group 2, and 1 patient in Group 1 (1.9%). FPF was positive in eight patients. The correlation of FDP and FPF was done by Fisher's exact test and was found to be statistically nonsignificant. Conclusion: In the present study, FDP was positive in 52 (96.3%) OSMF patients; hence, FDP may be used as an early indicator of OSMF. FDP was found to be positive in two patients with a habit of chewing betel quid without OSMF. It may be hypothesized that these patients are more likely to develop OSMF. Hence, the estimation of FDP may be used as a diagnostic test to predict an impending OSMF before it could manifest itself clinically. FPF was negative in some OSMF patients, may be because it is below the detectable range.